Baby led weaning: an integrative review of scientific evidence from 2011 to 2019 - Vilas Boas, Açucena Carfdoso; Neri, Mayara Márcia Silva; Silva, Cynthia Francisca Xavier Costa de Assis; Teixeira, Lílian Gonçalves (ABCS Health Sciences, 2020)
Introduction: Baby-led weaning (BLW) is an alternative approach to introducing food to infants that has become popular. Objective: To investigate the scientific evidence regarding the BLW method and its modified version, Baby-Led Introduction to Solids(BLISS). Methods: The research was carried out between June 2018 and June 2019, through the databases US National Library of Medicine National Institutes of Health (PubMed) using the following keywords: ‘BLW’, ‘Baby-led weaning’, ‘BLISS’, and ‘Baby-Led Introduction to Solids’. All original articles from in English published between 2011 and 2019 have been included. Results: Twenty-five studies were included in the analysis. Research on BLW/BLISS focused mainly on the themes: characteristics, behaviors and attitudes of mothers and children, knowledge of mothers and health professionals about feeding methods, weight and body mass index evaluation of children, evaluation of energetic and nutrient intake of children and evaluation of episodes of choking and gag reflex. Conclusion: Most research deals with BLW-related experiences and there is still little evidence on the method in terms of adequacy of energy and nutrient intake and growth in childhood. Positive points to child can be observed such as prolonged breastfeeding, greater independence when feeding and better response to satiety. The methods of food introduction do not differ in relation to the occurrence of episodes of choking.